2020
DOI: 10.3390/ijms21186684
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA Repair in Cancer Therapy: Toward a Multi-Target Approach

Abstract: Alterations in DNA repair pathways are one of the main drivers of cancer insurgence. Nevertheless, cancer cells are more susceptible to DNA damage than normal cells and they rely on specific functional repair pathways to survive. Thanks to advances in genome sequencing, we now have a better idea of which genes are mutated in specific cancers and this prompted the development of inhibitors targeting DNA repair players involved in pathways essential for cancer cells survival. Currently, the pivotal concept is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 204 publications
(227 reference statements)
0
15
0
Order By: Relevance
“…Therefore, further studies need to be performed to determine how inhibition of DSB repair by HDACi treatment will affect cancer cells’ destiny in their native tumor microenvironment. However, the inhibition of DNA repair has proven to be highly effective in combined treatment according to numerous clinical trials [ 66 , 67 ], and the proposed combination with HDACi was aimed to decrease toxic side effects for cancer patients, increasing the effectiveness of genotoxic drugs and targeting only cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies need to be performed to determine how inhibition of DSB repair by HDACi treatment will affect cancer cells’ destiny in their native tumor microenvironment. However, the inhibition of DNA repair has proven to be highly effective in combined treatment according to numerous clinical trials [ 66 , 67 ], and the proposed combination with HDACi was aimed to decrease toxic side effects for cancer patients, increasing the effectiveness of genotoxic drugs and targeting only cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some new results have been made in the studies which explored the relationship between DNA repair-related genes and cancers. A past study suggested that gene alterations in DNA repair pathways promoted cancer aggressiveness and induced the resistance to DNA damage cancer treatments [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although this situation is more complex, the answer appears to be yes. For example, a major component of current work on chemotherapy has the goal of finding compounds that specifically inhibit cancer cell biochemistry while doing minimal damage to healthy cell biochemistry [ 27 , 28 , 29 , 30 , 31 , 32 ]. The target is often DNA repair or DNA replication because of the more rapid DNA replication of tumor cells [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Phages and Phage Dna Packaging In Relation To Biomedicine: A...mentioning
confidence: 99%